A Cresol Vale Europeu e o crédito rural para a agricultura familiar na visão dos atores sociais - Marcos Catelli Rocha; Fábio Luiz Búrigo; Cristiano Desconsi (Ciências Sociais Unisinos)
This research is about the rural credit cooperative Cresol Vale Europeu, linked to the Central Cresol Baser, belonging to the Cresol System. The Cooperative was born at the end of 2018, through the incorporation of five singular cooperative that exist in the cities of ÁguasMornas, Botuverá, Ituporanga, São João do Itaperiú and Schröeder. Credit cooperatives in the solidarity financial system were created in the end of twentieth century to democratize financial services to the excluded population. Historically, rural credit for family farming was the main financial product of the Cresol System. This situation has been changing in recent years due to external factors to the cooperative and others factors. This research has studied how rural credit fits into this new environment of Cresol’s performance, analyzing its results, potentialities and limits in terms of cooperative governance and rural development. This investigation was carried out based on field research with social actors in the territory of cooperative’s operation, through semi-structured interviews with cooperative family farmers, technicians and managers. In their view, the results obtained by the Cooperative in its policies of rural credit for family farming are the fruit of a close work, which has managed, over time, to improve its governance in the face of the challenges imposed by the financial market. However, the main challenge lies in the paradox between ensuring the growth and expansion of the Cooperative and strengthening social ties that maintain a good relationship with the membership, especially the rural environment that is the origin of the Cooperative.